2013
DOI: 10.1111/j.1529-8019.2013.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in chronic urticaria: a retrospective series of 15 cases

Abstract: Omalizumab is a monoclonal anti-IgE antibody approved for the treatment of severe allergic asthma. There is increasing evidence in the literature of its usefulness in chronic urticaria. Herein, we report a retrospective case series of 15 patients with chronic idiopathic urticaria treated with omalizumab. We reviewed their medical records to assess the improvement achieved after 3 and 6 months of treatment. Complete response was defined as symptom disappearance that could be followed by discontinuation of antih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Further evidence of omalizumab efficacy was seen in two studies, the first in Spain and the second in France, both published in 2013. The Spanish study evaluated the effectiveness of omalizumab in 15 patients with CIU, 12 of whom responded within the first 3 months of treatment (three with complete response and nine with partial response) . At month 6, eight of 10 patients who continued omalizumab therapy had a complete response, with the two others having a partial response.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Further evidence of omalizumab efficacy was seen in two studies, the first in Spain and the second in France, both published in 2013. The Spanish study evaluated the effectiveness of omalizumab in 15 patients with CIU, 12 of whom responded within the first 3 months of treatment (three with complete response and nine with partial response) . At month 6, eight of 10 patients who continued omalizumab therapy had a complete response, with the two others having a partial response.…”
Section: Resultsmentioning
confidence: 94%
“…The Spanish study evaluated the effectiveness of omalizumab in 15 patients with CIU, 12 of whom responded within the first 3 months of treatment (three with complete response and nine with partial response). 17 At month 6, eight of 10 patients who continued omalizumab therapy had a complete response, with the two others having a partial response. On the other hand, the French study evaluated three patients with refractory chronic cold urticaria (CCU) and found the optimal dose and dosing interval to be a starting cycle of four subcutaneous injections of omalizumab 300 mg every 2 weeks, with subsequent injections given depending on the progression of the symptoms.…”
mentioning
confidence: 99%
“…Three (11.1%) patients were completely symptom-free and were able to discontinue treatment with omalizumab. Concurrently, Arment-Carbo et al [14] presented a case series of 15 patients treated with omalizumab of whom eight patients reported complete response after 6 months of treatment, although three out of the eight patients were only able to achieve complete response after an increase of omalizumab from 150 to 300 mg. Other real-life studies also suggested an individualized dosing regimen as the most efficient treatment plan [4,18]. Notably, a retrospective study by Metz et al [25••] of 25 patients with CSU and/or CINDU (mean age 45 years) investigated the response to omalizumab during retreatment.…”
Section: Dosing Regimensmentioning
confidence: 94%
“…The proportion of patients with no or very limited response to omalizumab in the 13 identified studies was, on average 15% (lowest 2% [18], highest 33% [14,16]). …”
Section: Main Findingsmentioning
confidence: 97%
“…Partial response (PR) Resolution or improvement of symptoms with the addition of antihistamines (Armengot-Carbo et al, 2013).…”
Section: Definitionsmentioning
confidence: 99%